A comparison of hydrogen storage capacity of commercial and fly ash-derived zeolite X together with their respective templated carbon derivatives. (5th October 2015) - Musyoka, Nicholas M.; Ren, Jianwei; Langmi, Henrietta W.; North, Brian C.; Mathe, Mkhulu
Abstract: This paper presents comparative results of structural, morphological and hydrogen sorption properties between commercial and fly ash-derived zeolite X including their respective templated carbon derivatives. The surface area of commercial zeolite was found to increase by 328% from 796 m 2 g −1 to 2578 m 2 g −1 upon templation process whereas that of fly ash-derived zeolite increased by 275% from 404 m 2 g −1 to 1112 m 2 g −1 on templation. The trend in hydrogen uptake was also proportionally mirrored by the surface area. Commercial analysis estimated that the cost of synthesizing zeolite X from fly ash is one fifth that of the existing commercial zeolite production process. The use of fly ash-derived zeolites is expected to present a cost effective and competitive way of producing zeolite templated carbons. Additionally, fly ash zeolitization together with its use in the synthesis of templated carbons also present an attractive way of beneficiating coal fly ash. Graphical abstract: Highlights: The study compared the use of commercial and fly ash-derived zeolites as templated for synthesis of carbons. Templated carbons had a higher hydrogen uptake than their parent zeolites. The use of fly ash-derived zeolites presents a cost effective and competitive way of producing templated carbons.